Photobooks dedicated to Gunkanjima: Random Personal Memories or Strategical Publications? - Cecile Laly (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This paper analyzes the photobooks produced by several Japanese and French photographers dedicated to the mining island of Hashima, better known today as Gunkanjima (Battleship Island). The publications were released mainly over the last two decades, around the time Japan began the UNESCO application proceedings for the Tentative List of “Sites of Japan’s Meiji Industrial Revolution: Iron and Steel, Shipbuilding and Coal Mining”, which includes a total of twenty-three sites, among which is Hashima. This paper will first examine how the photobooks pictorialize the island beginning from the 1950s, through the period of Japan’s high growth, up until the closure of the mine and the years of abandonment and decay that followed. It will then highlight how, in the context of dissonant heritage, the narrative of these photobooks built a positive image of the island in order for it to be considered a place worth inscribing as a World Heritage Site. It also shows how the mere existence of these numerous photobooks allowed Hashima to enter into the artistic heritage of Japan as an iconic muse.